ANALISIS PEMBANGUNAN BERBASIS SPASIAL DI KABUPATEN MADIUN - Andri Wijanarko (Trunojoyo University of Madura, 2013)
The Important part in the context of development planning is an evaluation of the development process. The evaluation is conducted to obtain feedback that can be recognized early divergence aberration implementation of development plans, and then can be formulated remedial measures are well targeted and timely. Evaluation can be done using several approaches as needed. This is no exception with Madiunn County, which consists of 206 administrative villages / urban (198 villages and 8 villages) are scattered in 15 districts.Based on the results of research, (A) SSWP 1 has a total population of 2012 amid the highest reaching 279 404. This is a potential for the development of human resources and labor potential in the labor market structure. (B) The existence of inequality and the number of junior high school graduates who are still concentrated in SSWP 1 and 3. (C) In the event that the number of poor people, it turns out SSWP 1 which has the highest number of population also has the highest number of poor people. Not less than 2,521 population recorded very poor; 7,931 poor and 7,573 near-poor population. (D) Based on the data values in the formal industrial investments throughout SSWP, it appears that SSWP 1 has the highest number with a total value of Rp 25,747,183,000, particularly in Sub Pilangkenceng amounting to Rp 6,958,750,000.